Therapeutic Decision Making in Acute Stroke due to Carotid Artery Dissection: A Potential Role for Percutaneous Vascular Intervention following Intravenous Thrombolysis. (21st February 2013) - Lewis, J. B.; Merwick, Á.; Laoide, R. Ó.; O'Hare, A.; McGuigan, C.
Abstract : Internal carotid artery dissection (ICAD) is an important cause of acute ischemic stroke in younger patients. Potential acute treatments include anticoagulation, intravenous thrombolysis (IVT), and endovascular thrombectomy (ET). We report a case where the use of IVT followed by ET resulted in a good clinical outcome in a patient with tandem internal carotid and middle cerebral artery occlusion following ICAD.